From Individual Suffering to Collective Struggle: Narratives of Engagement of Mothers in Social Movements (Revista de Estudos da Linguagem, 2024)
Rio de Janeiro is the state with the highest number of homicides due to police brutality (largely Black people). Faced with this situation and seeking justice, the victims’ mothers engage in social movements such as the Rede de Comunidades e Movimentos contra a Violência. This paper focuses on what I will refer to as the narratives of engagement of these family members, especially mothers. It aims to understand how important narratives are for these women in the process of transforming grief into political action. The methodology encompasses a qualitative-interpretative research approach with participant observation. The data was generated in the protests organized by the Rede. The analysis was guided by the notion of narrative as a discursive and interactional practice which organizes human experience. Such practice also serves as a tool for social movements to make demands of the state. The analysis suggests the existence of a pattern that organizes the narratives of engagement; it further identifies two discursive mechanisms that interact with each other: i) the rationalization of events leading to the death of their children by using coherence systems; ii) a spiral movement that relates microsocial and macrosocial events in the narrative. The article concludes by highlighting narratives of engagement as a tool for this social movement to raise its demands in the public sphere, as well as a way of resisting structural racism.